Evaluation of the bioprotectivity of Lactobacillus binary/ternary cultures in yogurt. Issue 9 (26th July 2020) - Fayyaz, Nasrin; Shahidi, Fakhri; Roshanak, Sahar
Abstract: The attempts toward addition of biocontrol agents in dairy products have gained popularity. Here, we worked on analysing the antifungal activity of binary and ternary combinations of three Lactic Acid Bacteria (LAB) against five spoilage yeasts in yogurt. The yogurt samples were characterized in terms of pH, acidity, WHC, textural parameters, viscosity, survivability and antifungal activity of LAB and sensorial properties during cold storage. The results showed that the inoculation of LAB in yogurt gave rise in significant reduction of pH throughout cold storage while titrable acidity and WHC decreased ( p  < .05). Inoculation of LAB resulted in significant increase in hardness and adhesiveness while springiness remained constant. On the other hand, apparent viscosity of all samples experienced a profound increase up to the 10th day of storage followed by a reduction trend for the rest of storage period. Analysis of inhibitory activity of LAB showed an efficient barrier against all five yeasts, in which the most activity was recorded for Lactobacillus reuteri followed by Lactobacillus acidophilus . On the other hand, the most resistance yeast was Kluyveromyces marxianus followed by Rhodotorula mucilaginosa . Sensorial analysis revealed that addition of LAB in yogurt brought about a profound improvement in textural quality of samples. Inoculation of LAB cultures in yogurt at 5% (v/v) not only could improve the physicochemical and sensorial properties of yogurt, but also could introduce a strategy toward substituting of chemical preservatives with biocontrol agents. Abstract : Inoculation of Lactic Acid Bacteria cultures in yogurt at 5% (v/v) not only could improve the physicochemical and sensorial properties of yogurt, but also could introduce a strategy toward substituting of chemical preservatives with biocontrol agents.